2023
DOI: 10.3390/microorganisms11102396
|View full text |Cite
|
Sign up to set email alerts
|

High Levels of IL-1β, TNF-α and MIP-1α One Month after the Onset of the Acute SARS-CoV-2 Infection, Predictors of Post COVID-19 in Hospitalized Patients

Jacobo Alonso-Domínguez,
María Gallego-Rodríguez,
Inés Martínez-Barros
et al.

Abstract: The pandemic caused by SARS-CoV-2 infection has left behind a new symptomatology called post COVID-19, or “long COVID”. The pathophysiological mechanisms still remain controversial; however, a link between persistent inflammation and these sequelae has been suggested. Herein, we longitudinally assessed up- and downstream molecules of the NLRP3 inflammasome’s pathway in three study groups: healthy donors (HC, n = 14) and donors with a confirmed SARS-CoV-2 infection who had been hospitalized, the latter divided … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
3
0
Order By: Relevance
“…Only female sex was found to be predictive of subsequent PCC. This finding is consistent with previous research, which highlights the notable association between the risk of PCC and specific socio-demographic factors, in particular female sex ( 19 ). Although some studies have hinted at possible links with ethnicity or pre-existing conditions (such as poor mental and general health or asthma), there is a lack of consistent evidence across studies to designate these as reliable predictors of PCC ( 20–22 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Only female sex was found to be predictive of subsequent PCC. This finding is consistent with previous research, which highlights the notable association between the risk of PCC and specific socio-demographic factors, in particular female sex ( 19 ). Although some studies have hinted at possible links with ethnicity or pre-existing conditions (such as poor mental and general health or asthma), there is a lack of consistent evidence across studies to designate these as reliable predictors of PCC ( 20–22 ).…”
Section: Discussionsupporting
confidence: 93%
“…Many studies have found a link between elevated ferritin levels and increased risk of death. However, the relationship is complex, and other factors can play a role ( 19 , 20 ). It should be noted that, to our knowledge, no previous research has specifically examined sex disparities in ferritin values among patients with mild COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Only female sex was found to be predictive of subsequent PCC. This finding is consistent with previous research, which highlights the notable association between the risk of PCC and specific socio-demographic factors, in particular female sex (19). Although some studies have hinted at possible links with ethnicity or pre-existing conditions (such as poor mental and general health or asthma), there is a lack of consistent evidence across studies to designate these as reliable predictors of PCC (20)(21)(22).…”
Section: Discussionsupporting
confidence: 89%
“…Notably, MIP-1α, along with MIP-3β, holds great importance in modulating the efficacy and polarization of antigen-specific immunity (35). Additionally, studies have shown that IL-1β can enhance the production of MIP-1α through the activation of NF-κB (27). These findings collectively underscore the significance of MIP-1α in COVID-19 and its association with immune responses and inflammation mediated by other cytokines.…”
Section: Discussionmentioning
confidence: 83%
“…Consistent with these findings, our study also identified a link between IL-1β and the severity of COVID-19. Interestingly, the elevated levels of IL-1β observed at month 1 in COVID-19 patients may not necessarily be attributed solely to increased reactive oxygen species (ROS) levels (27). Viral antigens could initiate the inflammasome pathway, contributing to the sustained production of IL-1β (28).…”
Section: Discussionmentioning
confidence: 99%